Turbine Power Production Sensitivity to Coastal Sheared and Turbulent Inflows. Issue 2 (April 2015) - Smith, Jamie C.; Carriveau, Rupp; Ting, David S-K
Inflows with identical wind speeds at turbine hub height can generate varying amounts of power, depending on parameters such as vertical shear and turbulence intensity. At a commercial wind farm located in Southwestern Ontario off the shores of Lake Erie, the wind profile approaching a multi-megawatt horizontal-axis turbine has been characterized by a meteorological mast and then correlated with resulting power production across a range of hub height speeds. Using data collected over a six-month measurement campaign, inferences have been drawn on the sensitivity of turbine performance to sheared and turbulent inflows for both land and lake-influenced winds at the coastal site under study.